A response adaptive design for ordinal categorical responses weighing the cumulative odds ratios. Issue 1 (1st January 2019) - Biswas, Atanu; Bhattacharya, Rahul; Das, Soumyadeep
ABSTRACT: Weighing the cumulative odds ratios suitably, a two treatment response adaptive design for phase III clinical trial is proposed for ordinal categorical responses. Properties of the proposed design are investigated theoretically as well as empirically. Applicability of the design is further verified using a data pertaining to a real clinical trial with trauma patients, where the responses are observed in an ordinal categorical scale.